THE ANALYSIS OF TEACHING WRITING TO ENGLISH YOUNG LEARNERS (EYL) THROUGH A MOVIE: AN ICT PERSPECTIVE - Paramita Kusumawardhani; Nurhayati Nurhayati (LPPM Universitas Bina Sarana Informatika, 2019)
This research has a purpose about using a movie to improve the learners’, especially English Young Learners’, writing skills. Movie, as a part of the development of technology, can be used to improve the learners’ writing skill. The participants of this research are English Young Learners (EYL) in of the English Course at Gading Serpong, Tangerang. Descriptive qualitative was used as the method of the research and the English Young Learners’ (EYL) story paper are used as the instruments of the research. The results of the research are: (1) Most learners were excited when they are asked to watch a movie; (2) Learners who have good writing skill could retell the story well, and (3) Learners who are not really master in writing, got some difficulties in retelling the story in written.